Organization of educational and industrial practice in the process of training specialists in the sphere of tourism - Щука, Галина (Pedagogy of Higher and Secondary Education, 2014)
Shchuka G. P. Organization of educational and industrial practice in the process of training specialists in the sphere of tourism. The article analyzes the level of organization of educational and industrial practice in the process of training of domestic bachelors tourism. The author assesses the normative duration of practices and installed the possibility of its prolongation; discusses the current technology designing of the process of practical training and are determined by its disadvantages; clarifies the principle of formation of the contents of practices and traced the existing communications theoretical and practical training.